Design of Book Donation Information System for the Bogor Reading Garden Community - Rivaldi, Fazar; Lestari, Mei; Parwati, Ni Wayan (Penerbitan Universitas Trisakti, 2024)
The Design of Community Administration Information System: A Case Study of Bogor Reading Garden Community. The research aims to streamline the data management and reporting processes for improved accuracy and enhanced organization through a computerized system. The designed system is integrated into a database. The chosen research method is Research and Development, a deliberate, systematic approach aimed at discovering, formulating, improving, developing, generating, and testing the effectiveness of superior, novel, efficient, productive, and meaningful products, models, methods/strategies, services, and procedures. By crafting the 'Design of Book Donation Information System for the Bogor Reading Garden Community' using Java Netbeans, it is anticipated to assist the secretarial department in administration processes and facilitate the creation of reports.